Operational resilience : (Financial World Pub., 2002)
This book describes how to develop a holistic framework for measuring, controlling, detecting, and responding to operational risk in all its manifestations. It provides the reader with a viable route to addressing this increasingly important issue in an effective and comprehensive manner.